2019
DOI: 10.2147/ott.s202122
|View full text |Cite
|
Sign up to set email alerts
|

<p>STAT gene family mRNA expression and prognostic value in hepatocellular carcinoma</p>

Abstract: Background Signal transducer and activator of transcription (STAT) proteins are well-known transcription factors that play an important role in the progression of cancer. However, the association between STAT family genes and hepatocellular carcinoma (HCC) remains unclear. This study investigates the expression level, the prognostic value and the potential mechanism of STAT family genes in HCC. Methods Data from 365 HCC patients in The Cancer Genome Atlas (TCGA) databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 30 publications
1
25
0
2
Order By: Relevance
“…In fact, another study about ccRCC also suggested that patients with higher TMB tended to be with a worse prognosis [45]. Moreover, Chuanjie et al found that ccRCC with higher TMB levels are associated with higher tumor grades and advanced pathological stages [46].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, another study about ccRCC also suggested that patients with higher TMB tended to be with a worse prognosis [45]. Moreover, Chuanjie et al found that ccRCC with higher TMB levels are associated with higher tumor grades and advanced pathological stages [46].…”
Section: Discussionmentioning
confidence: 99%
“…The STAT family could mediate various biological processes, including cellular immunity, invasion, differentiation, and apoptosis [27]. Activated by diverse cytokines, STAT signaling played a central role in immunity, cell death, and cancer pathogenesis and progression [8]. Extensive studies have revealed that STAT family exert important functions in cancers, such as hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Signal transducer and activator of transcription (STAT) signaling pathways are crucial for the function, proliferation, and apoptosis of immune cells, such as CD8 + cells and dendritic cells [6]. The aberrant activation of STAT signaling was confirmed to result in tumor pathogenesis and progress by regulating cell cycle, cell survival, and immune response [7,8]. STAT family consist of STAT1-4, STAT5A/5B, and STAT6.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that immune genes were related to the response and prognosis of HCC patients to immunotherapy [12]. Dong et al demonstrated that high expression of STAT5A, STAT5B, and STAT6 was associated with better prognosis in HCC patients [13]. This article proposed to identify a trustworthy model of HCC on the basis of immune genes, and demonstrated its clinical utility for HCC patients.…”
Section: Introductionmentioning
confidence: 97%